EFFECTIVENESS OF ETHANOL EXTRACT OF PURPLE EGGPLANT SKIN AS AN ANTIMALARIAL ON LIVER SIZE IN MICE INDUCED WITH Plasmodium berghei - Taniyo, Nurul Fadhilah; Muhammad In'am Ilmiawan; Muhammad Ibnu Kahtan; Sari Rahmayanti; Syarifah Nurul Yanti Rizki Syahab Assegaf (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Malaria is caused by the protozoa Plasmodium through the bite of the Anopheles mosquito, with one of the symptoms being an enlarged liver. This study aims to test the effectiveness of ethanol extract of purple eggplant (Solanum melongena L.) skin on the liver size of mice (Mus musculus) induced by Plasmodium berghei. Extraction was carried out by maceration using 70% ethanol. Mice were divided into treatment groups (extract doses of 0.075 mg/20 gBW, 0.15 mg/20 gBW, and 0.3 mg/20 gBW), positive control (DHP 3.744 mg/20 gBW), negative control (aquades), and normal control. Observations included parasitemia levels as well as liver weight, volume, and index. The results showed that the extract dose affected the liver size of mice. There was no significant correlation between parasitemia and liver weight (p=0.073) and volume (p=0.133), but there was a significant correlation with liver index (p=0.002). This study recommends further studies on the potential of active compounds in purple eggplant as hepatoprotective and antimalarial agents.